225k views
4 votes
Here are two steps from the derivation formula who took place between the first step and the second step

Here are two steps from the derivation formula who took place between the first step-example-1
User Landitus
by
5.2k points

2 Answers

3 votes

Answer:

Choice B is the answer.

Explanation:

We have given two step.

(x+b/2a)² = b²-4ac / 4a² Step I

a+b/2a = ±√b²-4ac / 4a² Step II

We have to choose the method to move step I to step II.

Taking square root to both sides of step I, we have

√(x+b/2a)² = √b²-4ac/4a²

As we know that

√x² = ±x

(x+b/2a) = ±√b²-4ac / 4a² and we get the step II.

Hence, the answer is choice B.

User Yash Chavda
by
5.5k points
4 votes

Answer:

B. Taking square root of both sides

Explanation:

The first step given to us is


(x+(b)/(2a) )^2=(b^2-4ac)/(4a^2)

When we take square root of both sides we obtain;


x+(b)/(2a)=\pm \sqrt{(b^2-4ac)/(4a^2) }

Therefore the corect answer is B

User SKulibin
by
5.6k points